REPRESENTING INTANGIBLE CULTURAL HERITAGE OF HUMANITY: FROM THE DEEP ABYSS OF THE PAST TO DIGITAL TWIN AND XR OF THE NEANDERTHAL MAN AND LAMALUNGA CAVE (ALTAMURA, APULIA) - F. Banfi; E. Dellù; C. Stanga; A. Mandelli; F. Roncoroni; S. Sivilli; G. Pepe; G. Cacudi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The Altamura Man and the paleontological remains are situated within a complex context encompassing logistical, geological, paleoenvironmental, and cultural perspectives. This context is exceptionally well-preserved but also fragile, requiring its preservation due to its unique nature. Unresolved inquiries exist in various disciplines, such as archaeology, biocultural studies, ecology, and geology, pertaining to karst formation, taphonomic dynamics, and the cultural and ecological context of the Neanderthal individual found in the cave. Interdisciplinary research was necessary to address these complex questions and understand the broader context of the Lamalunga Cave. Climate change also necessitated attention to preserving the cave’s microclimate and monitoring potential biodegradation. Digital technologies, including photogrammetry and laser scanning, were crucial for monitoring and safeguarding the cave’s cultural heritage. Digital representation, 3D modelling and Digital Twin were essential for managing the cave’s intricacies, analysing its values, and enhancing visual communication. The management of the Lamalunga cave aimed to promote scientific interpretation, safeguard the cave, and provide tools for understanding, storytelling, and further investigation. It was essential to utilise available methodologies and technologies while avoiding destructive interventions. Contemporary technologies have revolutionised the archaeological and paleoanthropological domains, enabling remote study and preservation. Protecting and comprehending the cultural heritage of the cave is linked to its usability, which can be enhanced through digital documentation methodologies to inform visitors about the karst context and promote social and economic development.